The role of ventral tegmental area in chronic stroke rehabilitation: an exploratory study - Astrakas, Loukas G.; Elbach, Sabrina; Giannopulu, Irini; Li, Shasha; Benjafield, Howard; Tzika, A. Aria (Frontiers, 2023)
Introduction: The acknowledged role of external rewards in chronic stroke rehabilitation, offering positive reinforcement and motivation, has significantly contributed to patient engagement and perseverance. However, the exploration of self-reward’s importance in this context remains limited. This study aims to investigate the functional connectivity of the ventral tegmental area (VTA), a key node in the brain’s reward circuitry, during motor task-based rehabilitation and its correlation with the recovery process.